Vermicompost tea in the production, gas exchange and quality of strawberry fruits - Mendonça, Gabriel Lobo de (2025)
The water-soluble extract from vermicompost, also known as vermicompost tea (VT), has attracted interest in sustainable production research due to its potential to increase crop yields. However, information regarding the influence of this bioinput on strawberry culti- vation remains limited. This study aimed to evaluate the effects of different VT solution concentrations on the mass fruit, physiology, and fruit quality of the hybrid strawberry cultivar ‘Portola’. The experiment was conducted in a greenhouse, with foliar and sub- strate applications of VT solutions at varying concentrations (0%, 2%, 4%, 6% and 8%) over 150 days. Evaluations included the chemical composition of the VT, as well as the physiological and agronomic parameters of the strawberry plants, such as gas exchange, biometric data, the physicochemical quality of the fruit and the nutritional composition. Significant differences in gas exchange parameters, particularly intercellular CO2 concen- tration and stomatal conductance, were observed at the final growth stage. Of the quality and compositional parameters of the strawberries, only the soluble solids/titratable acidity (SS/TA) ratio was affected. The various VT dilutions induced physiological alterations in the strawberry plants, with energy being allocated towards mass fruit at the expense of fruit quality, specifically in terms of the SS/TA ratio